Organization of medical aid with for the population with diseases of upper respiratory tract associated with chlamydia infection - T. A. Kapustina; A. N. Markina (Acta Biomedica Scientifica)
At the same time optima organization and. measures of treatment of extra-urogenital forms of chlamydiosis aren't developed yet and. this problem is needed to be solved. The article presents scientific basis of necessity of developement of complex of measures and. main directions that contribute to the organization of medical aid. for the people with infections of upper respiratory tract associated with chlamydiosis. 1827 people were examineds. First group included. l8—60 years old. employees of several enterprises (846 people) and. 3—17 years old. children attending kindergarten and school (483 childern). Second group included patients of ENT-ward of institute's clinics with, inflammatory pathology of upper respiratory tract (498 people) of 3—60 years old. including 246 childern and. 252 adults. Programme of optimization of medical aid. for people with chlamydia infection of upper respiratory tract that included complex of measures with directions divided into 4 main parts (organization and. performing, information. and. analytics, treatment, diagnostics and. prophylactics, study and. methodology). This programme can be the basis of development of system of medical aid for people with respiratory chlamydiosis by public health service agencie of Russian Federation subjects that contributed to the increase of effectiveness of treatment, diagnostic and. preventive measured. Algrorhythms of diagnostics developed by the authors are offered to use as diagnostic standards of chlamydia infection of upper respiratory tract for phycisians of different duties (otolaryngologists, therapeutists, pediatritians, phycisians of common duty, infectionists etc.).